Sixth Order Numerical Iterated Method of Open Methods for Solving Nonlinear Applications Problems: Sixth Order Numerical Iterated Method of Open Methods for Solving Nonlinear Applications - Qureshi, Umair Khalid; kalhoro, Zubair Ahmed; Shaikh, Asif Ali; Jamali, Sanaullah (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
This paper aims to construct a numerical iterated method of open methods to find a single root of application problems. The proposed numerical iterated method is the sixth order of convergence, and which is based on Steffensen Method and Newton Raphson Method. The proposed sixth-order numerical iterated method is compared with the Modified Efficient Iterative Method and Generalize Newton Raphson Method [16-17]. C++/MATLAB is used on a few examples for justification of the proposed method based on the number of evolutions, accuracy, and iterations. From numerical results, it has been observed that the sixth order numerical iterated method is good accuracy with good convergence criteria as the assessment of existing methods for solving the root of nonlinear applications problems.